Prevalence and risk factors for vitamin D insufficiency and deficiency at birth and associated outcome. Issue 1 (December 2016) - Marshall, Ian; Mehta, Rajeev; Ayers, Charletta; Dhumal, Smita; Petrova, Anna
Abstract Background Occurrence and consequence of cord blood (CB) vitamin D insufficiency/deficiency has not been adequately explored despite rising concern regarding this topic in pediatrics. This study was designed to determine the rate, maternal risk factors, and clinical outcomes in infants in association with vitamin D insufficient/deficient status at birth. Methods American Academy of Pediatrics (AAP) defined levels (ng/mL) were utilized to categorize the vitamin D status in CB samples as deficient (5–15), insufficient (16–20), and sufficient (21–100). We used descriptive statistics and multiple regression models to identify the rate and factors associated with vitamin D deficiency/insufficiency and related outcomes in the enrolled mother-infant pairs. Results This prospective study was conducted at a single center on postpartum women and their infants. Vitamin D deficiency and insufficiency was recorded in 38.9 and 29.8% respectively of the 265 CB samples. Deficient CB vitamin D levels in infants were associated with maternal Black, Hispanic, or Asian race/ethnicity, younger age, and increased number of pregnancies. The likelihood for infants to be born with an insufficient vitamin D level increases with younger maternal age and the number of pregnancies as well as Asian ethnicity. We did not find an association between the vitamin D status at birth and pre-discharge clinical characteristics of the neonates. Conclusions The likelihood for an infant to be born with vitamin D deficiency/insufficiency is relatively high and is related mainly to younger maternal age, gravidity, and non-White race/ethnicity. Our findings raise a question regarding the adequacy of the AAP recommended vitamin D supplementation requirements without knowing the infant's vitamin D status at birth.